Tourist assessment of the main axes of land roads in Tartus governorate - سليمان, باسل; جلال خضرة, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
In many regions of the world, road travel is one of the most popular ways travelers interact with the landscape and regional attractions around them. Tourist paths are chosen according to various considerations. The best tourist path may be the path that requires less time to cross, the path with the shortest distance, or the most beautiful path (with the greatest tourist weight). Tartus governorate contains a highway linking the governorate with both Homs and Lattakia governorates, and several secondary arterial roads linking the city with the regions. The research aims to evaluate the central road network in Tartous Governorate, according to the tourist importance of the area that passes through it and what it contains of natural, religious, cultural and archaeological tourist attractions, and to determine the tourist importance of each part of the road axes according to its proximity and distance from the tourist attractions. It uses a cumulative analysis of the intersections of tourist sites with the axes of main and secondary roads in the governorate to identify “physical” landscape features that may be visible or hidden from the road, and to determine the best tourist routes using a Network Analyst.